Perent's role in the process of transition - Chakiashvili-Kalmakhelidze, Ia ("Intercultural Dialogues" Transactions, 2023)
Transition, parent, preschool institution, special educational need, ready for school, Transition from the school institution to the school educational environment,is very important event for every child.On the basis of researches,we can say that starting school positively is the key to future academical and social success for children.Go through the process of transition is very significant factor for the children who have special educational needs and limited abilities. And in order for the transition to school to be painless, support of parents and cooperating with them is very important, as well as determine the needs of the children and the needs of the parents. Parents, pre-school institution, school should share responsibilities and duties equally. To raise parents' awareness of issues relevant to them, as a result of successful mutual cooperation, adjust each link (kindergarten, parent, school) to the child's needs. The study of the experiences of parents of children with special needs was a part of the general research conducted within the framework of the project "Study of the Transition of Children with Special Needs in the school, on the Example of Schools of Telavi Municipality" funded by the United Nations Children's Fund. In school transition parents of 5 children with special needs were selected. The purpose of the research was to describe the role, function, responsibilities and communication of the parents involved in the process of transition of children with special needs. The parents were interviewed using the interview method. As a result of the research, the strengths and challenges of the transition process were identified. Certain conclusions were drawn and relevant recommendations were developed. The parent believes that the main challenge is the process of adapting the child to the school environment. Emphasizes the importance of the process of preparation of the child and parents in the preschool period. Especially mentions the support of the school and the early development center, early intervention services, the child's involvement with the school representatives and the meetings of the center's specialists, both in the assessment and subsequent processes.